2020
DOI: 10.1136/jitc-2020-001560
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of immunotherapy with activated natural killer cells and anti-GD2 antibody dinutuximab prior to resection of primary neuroblastoma prolongs survival in mice

Abstract: BackgroundImmunotherapy with anti-disialoganglioside dinutuximab has improved survival for children with high-risk neuroblastoma (NB) when given after induction chemotherapy and surgery. However, disease recurrence and resistance persist. Dinutuximab efficacy has not been evaluated when initiated before primary tumor removal. Using a surgical mouse model of human NB, we examined if initiating dinutuximab plus ex vivo-activated natural killer (aNK) cells before resection of the primary tumor improves survival.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Upregulation of TIM3 on CD8 + T cells and TIM3 ligand on tumor cells induced by OVs contributed to the resistance to PD-1 blockade. This study suggested that targeting multiple ICB pathways is a rational approach to overcome resistance to single ICB treatment and achieve optimal synergy with OVT [ 134 ].…”
Section: Ovs In Combination With Immunotherapymentioning
confidence: 99%
“…Upregulation of TIM3 on CD8 + T cells and TIM3 ligand on tumor cells induced by OVs contributed to the resistance to PD-1 blockade. This study suggested that targeting multiple ICB pathways is a rational approach to overcome resistance to single ICB treatment and achieve optimal synergy with OVT [ 134 ].…”
Section: Ovs In Combination With Immunotherapymentioning
confidence: 99%
“…Among them, the anti-GD2 monoclonal antibody dinutuximab (ch14.18) has been approved by the US Food and Drug Administration, and dinutuximab β (ch14.18/ CHO) has been approved by the European Medicines Agency for high-risk neuroblastoma treatment. 8 Nevertheless, GD2 antibodies can cause severe side effects, such as capillary leak syndrome, hypersensitivity reactions, intense neuropathic pain, infection, and fever. The root of these side effects is that although GD2 is overexpressed on NB tumor cells, it is also expressed in low amounts on peripheral nerves, peripheral sensory nerve fibers, mesenchymal stem cells, brain parenchyma, etc.…”
Section: Dovepressmentioning
confidence: 99%
“…Therefore, these properties make GD2 a promising target for NBtargeted therapy. 8 To date, GD2 has been treated as an attractive antigen for NB drug development and has great potential to achieve substantial clinical benefits in NB therapy. Several anti-GD2 antibodies have been evaluated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the availability of clinical grade cytokines and artificial antigen presenting cells (aAPCs), infusion of high numbers of purified, ex vivo activated NK cells are emerging from preclinical models into clinical trials. NK cells have already been shown to have cytotoxicity in vitro against a variety of NBL cell lines ( 17 ) and primary patient tumors ( 18 , 19 ) as well as in vivo with xenograft NBL models ( 20 ). In addition, the lymphopenic environment induced from the conditioning regimen for allogeneic HSCT is conducive for NK cell expansion given the presence of high levels of IL-15 ( 21 ).…”
Section: Introductionmentioning
confidence: 99%